Biodiversity of Sea Urchin in the Area of Sari Ringgung Beach, Pesawaran Regency, Lampung - Mulyana, Jeane Siswitasari; Melinia, Nur Astri; Maretta, Gres (Universitas Labuhanbatu, 2023)
Echinoderms have specific characteristic in the form of spines or protrusions on its body surface. The class of Echinoidea or commonly known as sea urchin is one of the extant members of Echinoderms with ecologically and economic pivotal roles. Habitat of sea urchin is a hard bottom with a mixture of coral reef ecosystems, seagrass beds, and sand and coral debris. In the area of Sari Ringgung Beach, coral reefs and seagrass ecosystems are quite extensive. The purpose of this study was to investigate sea urchin species and analyze its population, relative abundance, diversity index, and dominance index. This research used purposive sampling method based on substrate type criteria. The sea urchin found were identified using the Clark & Rowe (1971) identification book. Two species of sea urchin were found and identified as Diadema sp. and Brissus sp. Individual abundance values ranged from 0-0.027 ind/m2, relative abundance values ranged from 0-96.67%, sea urchin species diversity index was low, ranging from 0-0.5982, and was dominated by sea urchin types of Diadema sp. at station 2 of 0.9356